Efficacy of autologous platelet-rich plasma versus corticosteroid injections in degenerative facet joint syndrome - Jayakrishnan, Aryadev; Seenappa, Hariprasad (International Journal of Research in Orthopaedics, 2026)
Background: Degenerative Facet Joint Syndrome (DFJS) is a common cause of chronic low back pain, particularly in the elderly. Current treatments, including intra-articular corticosteroid (CS) injections, offer short-term relief but are associated with adverse effects. Autologous platelet-rich plasma (PRP) injections have emerged as a potential alternative due to their regenerative properties and minimal side effects. This study compares the efficacy of single intra-articular PRP versus CS injections in managing DFJS. To evaluate and compare the short- and long-term functional outcomes of intra-articular PRP and CS injections in patients with DFJS. Methods: This prospective, randomized controlled trial included 74 patients diagnosed with DFJS, randomly divided into two groups. Group A (n=37) received a single intra-articular PRP injection, while Group B (n=37) received a single intra-articular CS injection. Outcomes were assessed using the Visual Analog Scale, Present Pain Index, Modified Oswestry Disability Index, Roland-Morris Questionnaire, and Short Form Health-12 at 4 weeks, 8 weeks, 12 weeks, 6 months, and 1-year post-injection. Results: Both groups showed significant reductions in pain and disability scores. In the short term, the CS group demonstrated greater improvement, though not statistically significant. However, at 1 year, the PRP group showed superior outcomes in pain reduction, functional ability, and quality of life, with long-term benefits surpassing those of CS. Conclusions: Intra-articular PRP injections offer a safe and effective treatment option for DFJS, providing longer-lasting relief compared to CS. While both treatments are beneficial, PRP may be the preferable choice for patients seeking sustained improvement in pain and functionality.